EDUCATION ENGLISH LANGUAGE STUDENTS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
English language proficiency is a fundamental skill that enables students to communicate effectively, access global knowledge, and succeed academically. This paper explores the importance of developing English language skills in students and presents effective strategies for fostering these skills in educational settings. It discusses the role of immersive learning, communicative approaches, and technology in enhancing students’ language abilities. The study also highlights the challenges teachers face in promoting English proficiency and suggests practical solutions. Developing English language skills prepares students for academic success and equips them with essential communication skills for future opportunities.